2020
DOI: 10.1038/s41598-020-74179-6
|View full text |Cite
|
Sign up to set email alerts
|

Dermal fibroblasts have different extracellular matrix profiles induced by TGF-β, PDGF and IL-6 in a model for skin fibrosis

Abstract: Different stimulants might induce different extracellular matrix profiles. It is essential to gain an understanding and quantification of these changes to allow for focused anti-fibrotic drug development. This study investigated the expression of extracellular matrix by dermal fibroblast mimicking fibrotic skin diseases as SSc using clinically validated biomarkers. Primary healthy human dermal fibroblasts were grown in media containing FICOLL. The cells were stimulated with PDGF-AB, TGF-β1, or IL-6. Anti-fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 50 publications
6
64
1
Order By: Relevance
“…This is not surprising as both PRO-C3 and PRO-C6 are biomarkers of collagen formation derived from fibroblasts and thus correlate directly to fibroblast activity. 24 Both markers are well known to be associated with increased severity of fibrosis and portal hypertension. 5 , 7 , 17 Interestingly, the plasma levels of the collagen type IV formation marker PRO-C4 were similar between patients with AD and ACLF.…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising as both PRO-C3 and PRO-C6 are biomarkers of collagen formation derived from fibroblasts and thus correlate directly to fibroblast activity. 24 Both markers are well known to be associated with increased severity of fibrosis and portal hypertension. 5 , 7 , 17 Interestingly, the plasma levels of the collagen type IV formation marker PRO-C4 were similar between patients with AD and ACLF.…”
Section: Discussionmentioning
confidence: 99%
“…This cell type has been widely used to study fibrotic behavior. [ 61–63 ] The cells were cultured in Dulbecco's modified Eagle's medium supplemented with 1% penicillin/streptomycin and 10% fetal bovine serum (Thermo Fisher). The fibroblasts were dispersed in a pre‐gel solution (1 × 10 6 cells mL –1 ) and photocrosslinked to encapsulate into a hydrogel.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, TGF-β1 increased the synthesis of type I collagen measured by COL1A1 mRNA and the biomarker PINP but not type III collagen synthesis measured by COL3A1 mRNA or the biomarker PRO-C3. Treatment of normal human dermal fibroblasts with TGF-β1 also resulted in increased type I collagen but not type III secretion or deposition [ 50 ]. Although TGF-β1 increased PRO-C6 in the conditioned media, this was most likely due to concurrent increases in cell numbers, as TGF-β1 reduced COL6A1 mRNA levels in the CoReFs.…”
Section: Discussionmentioning
confidence: 99%
“…Although TGF-β1 increased PRO-C6 in the conditioned media, this was most likely due to concurrent increases in cell numbers, as TGF-β1 reduced COL6A1 mRNA levels in the CoReFs. Juhl et al [ 50 ] found that TGF-β1 downregulated COL6A1 in normal human dermal fibroblasts.…”
Section: Discussionmentioning
confidence: 99%